Identification and Count of the Active Sites in Olefin Polymerization Catalysis by Oxygen Quench. Issue 18 (1st July 2014) - Cipullo, Roberta; Mellino, Simona; Busico, Vincenzo; Sun, Wen‐Hua
<x xml:space="preserve">Abstract</x> A simple method for the counting and structural elucidation of the different active sites in an olefin polymerization catalyst system is introduced, based on a reaction quench by O2 under controlled kinetics, followed by NMR analysis of the OH‐labeled chain end‐groups formed upon acidic work‐up of the polymer. The method is successfully benchmarked using a molecular bis(phenoxyamino)Zr(IV)‐based catalyst characterized by a comparatively long‐lasting controlled kinetic transient at room temperature. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>